Canonization and Decanonization : Papers presented to the International Conference of the Leiden Institute for the Study of Religions (LISOR) held at Leiden 9-10 January 1997. - Kooij, Arie van der, 1945-; Toorn, K. van der.; Snoek, Joannes Augustinus Maria, 1946- (Numen Book Series, 1998)
This volume contains the papers read at the Leiden Conference on Canonization and Decanonization of 9-10 January 1997. The emphasis in this rich and wide-ranging contribution to the subject is on the processes of canonization and decanonization in several religions and on the phenomenon of religious canons as well. It has two sections: (De)canonization and the History of Religions, and (De)canonization and Modern Society. In the first section processes out of which canons eventually emerge are highlighted in contributions devoted to particular religions, viz. African religions, Judaism and Christianity, Islam, Buddhism and Zoroastrianism. The articles of the second section are of particular relevance to the contemporary situation in the western world, dealing with aspects such as forms of the survival of a canon in processes of modernization, canonization and the challenge of plurality, and canonization and hermeneutics. The reader may benefit even more from this volume as it contains also An Annotated Bibliography on the subject.